3D genome-selected microRNAs to improve Alzheimer's disease prediction - Li, Keyi; Chi, Runqiu; Liu, Liangjie; Feng, Mofan; Su, Kai; Li, Xia; He, Guang; Shi, Yi (Frontiers in Neurology, 2023)
Introduction Alzheimer's disease (AD) is a type of neurodegenerative disease that has no effective treatment in its late stage, making the early prediction of AD critical. There have been an increase in the number of studies indicating that miRNAs play an important role in neurodegenerative diseases including Alzheimer's disease via epigenetic modifications including DNA methylation. Therefore, miRNAs may serve as excellent biomarkers in early AD prediction. Methods Considering that the non-coding RNAs' activity may be linked to their corresponding DNA loci in the 3D genome, we collected the existing AD-related miRNAs combined with 3D genomic data in this study. We investigated three machine learning models in this work under leave-one-out cross-validation (LOOCV): support vector classification (SVC), support vector regression (SVR), and knearest neighbors (KNNs). Results The prediction results of different models demonstrated the effectiveness of incorporating 3D genome information into the AD prediction models. Discussion With the assistance of the 3D genome, we were able to train more accurate models by selecting fewer but more discriminatory miRNAs, as witnessed by several ML models. These interesting findings indicate that the 3D genome has great potential to play an important role in future AD research.